2017
DOI: 10.1080/1120009x.2017.1404287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility ofUreaplasmaspecies andMycoplasma hominisin Greek female outpatients, 2012–2016

Abstract: Mycoplasma hominis and Ureaplasma species are opportunistic pathogens associated with urogenital infections, complications during pregnancy and postpartum infections. Appropriate empirical antimicrobial treatment is necessary to achieve an optimal therapeutic outcome. This study evaluated the prevalence and the antimicrobial susceptibility of Mycoplasma hominis and Ureaplasma spp. isolated from 1,008 endocervical samples of outpatients in Crete, Greece, during a five-year period (2012-2016), using the commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…(25.7%), in agreement with other studies. 7,[40][41][42] However, Mh infection did not manifest the high bacterial loads expected as a result of the association with BV. 43 With 68.6% of the samples with <10 4 CFU/ml, our results indicated that BV was associated with the type of genital mycoplasma but not with the bacterial load.…”
Section: Discussionmentioning
confidence: 86%
“…(25.7%), in agreement with other studies. 7,[40][41][42] However, Mh infection did not manifest the high bacterial loads expected as a result of the association with BV. 43 With 68.6% of the samples with <10 4 CFU/ml, our results indicated that BV was associated with the type of genital mycoplasma but not with the bacterial load.…”
Section: Discussionmentioning
confidence: 86%
“…Doxycycline was proved the most active choice for the treatment of Mycoplasma hominis . 13 , 14 Quinolones or tetracyclines were active against Mycoplasma hominis and moxifloxacin appeared to have the greatest activity as the most effective therapeutic agent. 15 The patient in our case therefore switched to the right regimen of the combination of moxifloxacin and doxycycline with a marked improvement of clinical syndromes and a favorable result.…”
Section: Discussionmentioning
confidence: 99%
“…El aumento de resistencia a macrólidos por parte de Ureaplasma urealyticum ha sido reportado en diversas partes del mundo, lo que ha generado una preocupación en relación a la reducción del arsenal terapéutico en el caso de las embarazadas, en quienes está contraindicado el uso de tetraciclinas, y en relación a quinolonas (categoría C de la Food and Drugs Administration, FDA) son contraindicadas por muchos autores, y alternativa secundaria por algunos "cuando el beneficio supera al riesgo" (4)(5)(6)(7)(8)(15)(16)(17) .…”
Section: Discussionunclassified